Effectiveness and Safety of the Korean Medicine Senior Health Promotion Program Using Herbal Medicine and Acupuncture for Mild Cognitive Impairment: A Retrospective Study of 500 Patients in Seoul, Korea. (6th December 2021) - Suh, Hyo-Weon; Seol, Jae-Hyun; Bae, Eun-Joo; Kwak, Hui-Yong; Hong, Sunggyu; Park, Yong-Sin; Lim, Jae Hwan; Chung, Sun-Yong
Abstract : Background . The management of mild cognitive impairment (MCI) is becoming increasingly important. The Korean Medicine Senior Health Promotion Program (KSHPP) was developed in 2016, and it has been in use to date. This study aimed to assess the effectiveness of KSHPP using herbal medicine and acupuncture for treating MCI and the safety of herbal medicine using liver and renal function tests. Methods . We retrospectively reviewed the medical records of the participants with MCI. We assessed the Korean version of the Montreal Cognitive Assessment (MoCA-K), the Mini-Mental State Examination-Dementia Screening (MMSE-DS), and the Geriatric Depression Scale Short Form-Korea version (GDSSF-K) scores before and after KSHPP to determine its effectiveness. To evaluate its safety, the liver and renal function tests were conducted before and after herbal treatment. Results . We enrolled 1002 participants, and 500 participants satisfied the inclusion criteria. Of 500 patients, 364 (72.8%) were depressed and 136 (27.2%) were not. The mean MoCA-K score significantly increased by 2.77 for the entire sample and 3.22 for the depressed sample (all P < 0.0001 ). The mean MMSE-DS score significantly increased by 2.19 for the entire sample and 2.51 for the depressed sample (all P < 0.0001 ); the mean GDSSF-K score significantly decreased by 1.73 for the entire sample and 2.68 for the depressed sample (all P < 0.0001 ). Conclusions . Our findings suggest that Korean medicine interventions can improve cognitive function and depression symptoms in patients with MCI. In addition, the results of the liver and renal function tests were analyzed as surrogate outcomes to assess the safety of herbal medicine. Based on these results, we expect that Korean medicine interventions can promote the cognitive and mental health of seniors. However, as there were several study limitations, particularly study design, practice effect, and short follow-up, these results must be interpreted with caution. We need a further long-term study with a rigorous design to retain confidence in the effectiveness and safety of KSHPP.